A Comparative Analysis of the Predictors, Extent and Impacts of Self-stigma in Patients with Psoriasis and Atopic Dermatitis - Sophie Schlachter; Rachel Sommer; Matthias Augustin; Athanasios Tsianakas; Lukas Westphal (Medical Journals Sweden, 2023)
The impact of dermatological diseases goes beyond symptoms and often includes psychosocial burden. Self-stigmatization plays a key role in this relationship and was compared in patients with psoriasis and atopic dermatitis to evaluate the validity of cross-disease stigmatization models. In total, 101 patients per indication were included in this cross-sectional study. Besides sociodemographic and clinical data, patient-reported outcome measures relating to self-stigmatization, depression, anxiety, and quality of life were compared across groups. Sociodemographic and clinical factors were tested for their moderating effects between self-stigmatization and quality of life. Group mean comparisons yielded no significant differences in self-stigmatization between patient groups. In both diseases, self-stigmatization significantly predicted depression and anxiety symptoms as well as quality of life. Current symptoms, not having close social relationships, and lower age predicted self-stigma in patients with psoriasis, whereas the involvement of sensitive body areas, the sum of previous treatments, and female sex were predictors in patients with atopic dermatitis. In both groups, symptoms had significantly moderating effects. The results underline the relevance of self-stigmatization in patients with chronic skin diseases. Awareness should be raised, screening implemented, and psychosocial support offered early on. Assessments, conceptual models of self-stigma, and interventions are probably applicable for both diseases.